THE RELATIONSHIP BETWEEN SELF-ESTEEM AND INTIMATE FRIENDSHIP WITH SELF-DISCLOSURE IN ADOLESCENTS WHO USE INSTAGRAM SOCIAL MEDIA - Dias, Celin; Widyastuti, Widyastuti (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aimed to investigate the relationship between Instagram use and self-disclosure among adolescents, focusing on how self-esteem and the quality of close personal relationships influence their online social expression. Method: A total of 204 adolescent Instagram users participated in this quantitative study. Data were collected using three validated psychological scales: the self-esteem scale (α = 0.882), the close friendship scale (α = 0.896), and the self-disclosure scale (α = 0.853). Data analysis was conducted using Pearson correlation with SPSS 25 for Windows. Results: The findings revealed a significant positive correlation (r = 0.662, p < 0.05) between self-esteem, close friendships, and self-disclosure. Furthermore, 64.3% of the variance in self-disclosure was explained by self-esteem and the quality of personal relationships, indicating that adolescents with higher self-esteem and stronger close friendships are more likely to engage in self-disclosure on Instagram. Novelty: This study highlights the role of Instagram as a digital space for adolescent self-expression and provides empirical evidence on the psychological factors that enhance self-disclosure in social media contexts, offering valuable insights for digital literacy and youth mental health initiatives.